Stability and Change in Rhythmic Patterning Across a Composer's Lifetime: A Study of Four Famous Composers Using the nPVI Equation. - Patel, Aniruddh D.; Daniele, Joseph R. (Tufts University. Tisch Library., 2016)
Historical trends in the rhythm of Western European instrumental classical music between ∼1650 and 1950 have recently been studied using the nPVI equation. This equation measures the average degree of durational contrast between adjacent events in a sequence (such as notes in a musical theme) These historical studies (e.g., Daniele & Patel, 2013, Hansen et al., in press) have relied on assigning each composer's music a mean nPVI value in order to search for broad historical trends across composers. Here we address how mean nPVI might vary across different compositional periods within a composer's lifetime, focusing on four famous composers whose lives have been demarcated into different epochs by historical musicologists, and who were part of Daniele and Patel's original study: J. S. Bach, Mozart, Beethoven, and Brahms. For these composers, we find that the mean nPVI does not vary dramatically across compositional periods. Nevertheless, there are interesting trends within the lifetime of each composer which reflect the larger 'rising nPVI' trend seen across all Austro-German composers studied by Daniele and Patel (2013) These findings demonstrate the utility of studying historical patterns in musical rhythm at two distinct timescales: within the lifetimes of individual composers, and across composers from divergent musical eras.